Investigation on Mechanical Behaviour of LM6 Aluminum Alloy Hybrid Composites Processed Using Stir Casting Process - S. Suresh Pungaiah; Kuldip Kumar Sahu; R. Yuvaraja; G. Jayahari Prabhu; R. Raja Sudharsan; P. Thamizhvalavan; Kiran Ramaswamy (Advances in Materials Science and Engineering)
The stir casting process produces boron nitride (B4N) and fly ash-based LM6 metal matrix composites. This hybrid composite was fabricated by varying fly ash from 3% to 15% with an increase of 3%. While the other reinforcement B4N concentration was kept constant as 3%. The morphology of the metal matrix composite is analysed using a light optical microscope. The microstructure analysis shows the uniform distribution of hybrid reinforcement throughout the matrix, and only a few clusters are found in the matrix alloyed with 15% B2N. Both pure and reinforced matrices are evaluated for the mechanical properties’ evaluation. The result shows an increment in hardness from 70.4 VHN to 96.2 VHN. Similarly, the tensile strength of the composite material is improved from 151 MPa to 192 MPa. The reason for improving strength and hardness is the uniform distribution of hybrid reinforcement in the LM6 matrix.